Healthcare Service System for the elderly and Thailand 4.0 Model - บุญเชียง วราภรณ์; ทองดี จีราพร (Nursing Journal CMU, 2017)
Dealing with the fast-growing aging population, the development of healthcare services is required in order to respond to the problems and needs of the elderly. Even though the evolution of medicine and technology can help humans to live longer, the following trend of greatly increasing cost of healthcare in the elderly lead to not having enough coverage for care. Therefore, the health technology will be included as a tool for disease prevention, providing information and rehabilitation for older people with the target of getting an access to the health services and receiving the quality, equity, and effectiveness of care. Thailand’s government policy seeks to develop the country towards Thailand 4.0 model, which was conducted along with economic reform driven by the application of technology, creativity, and innovations well as increasing focus on service sector. The 5 target technology and industrial groups include:1) food, agriculture and biotechnology, 2) public health, health, and medical technology, 3) digital equipment, robot, and electronic mechanical control systems, 4) digital technology and internet connection to control devices, and 5) innovation industry, culture, and high value service. This policy stated above can affect the development of healthcare service system for older people that responds to the demand of the problem and current situation of the aging population and in the future that the number of the elderly increasing rapidly is a chance to develop the effectiveness of health services system for older people. Especially nurses play an important role in providing health services for the elderly. They need to rethink the way in which nurses provide health and care services for elderly and in particular how smart technologies. This is one of the Performance of nurses that are used to optimize the health and wellbeing of elderly.